Alexander Hotel Logo - Sya'bani, Mohammad; Maulina, Rini (Universitas Komputer Indonesia, 2024)
Alexander Hotel is located in the tourist area of Tegal City, Central Java, established since 1990, managed by PT Griya Wisata Hotel Management and Consultant. The identity of Alexander Hotel needs to reflect the hotel's strong vision and mission, one of which is through the logo. In the hospitality industry, the logo has a central role as an element of brand representation, the logo is not only a symbol, but the image of the company that is first seen by consumers and plays an important role in creating a positive brand perception. The existing Alexander hotel logo is inconsistent, there are differences in various media placement, whereas good consistency in logo use will strengthen the impression of desirability and increase guest confidence in the hotel. The purpose of this research is to find differences in the Alexander Hotel logo in various media placements. The method used is descriptive, data collection through observation and literature. The results of the study found that there are differences in logos at various hotel facilities, there are 6 different logo forms with three types of logos, namely monograms, combination logo marks and wordmarks. The benefit of the research is to contribute to the development of visual identity theory, especially in the context of the hospitality industry.